(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
Enhancing the effectiveness of education quality has always been and remains one of the main principles of state policy in the field of education. Improvement and efficiency in education quality are impossible without highly professional and skilled pedagogical staff. The development of pedagogical personnel can be ensured only through the continuous improvement of their education. An educators’ self-education and self-improvement are ongoing processes that require continuous development and are influenced by various educational, social, psychological, and health-related factors. Each of these factors has both positive effects — supporting the teacher in their processes of self-development and self-improvement — and negative effects that hinder these processes. Without competent and well-developed teachers who act in accordance with the demands of the time, it is impossible to ensure quality education. The purpose of the study is to analyze and present the essence of educators’ self-improvement and self-development processes, as well as the factors that contribute to or stop their continuity and consistency. The scientific study of self-improvement and self-development processes is important not only for pedagogical theory but also for educational policy and practice.